(untitled) (Tzintzun, Revista de Estudios Históricos, 2019)
The managerial technocracy had its first expression in Chile in the government of Jorge Alessandri Rodríguez, an eclectic liberal. Indeed, who ruled between 1958 and 1964 was characterized by a first phase of his government that included Cabinet Managers, obeying various influences technocratic and depoliticizing against the traditional form of partisan political administration.